(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
1 - La questione, cruciale nelle società multiculturali, dell’uso della simbologia religiosa è tornata sotto la supervisione della Corte europea dei diritti umani, che già se n’era occupata più volte per i segni portati attraverso o per complemento dell’abbigliamento personale e una volta anche per quelli esposti nei luoghi pubblici. Stavolta si trattava di citazioni, o meglio allusioni, evangeliche utilizzate a scopo di marketing da un’azienda lituana che produce vestiti: tre manifesti, diffusi anche sul web, con la foto di un uomo e una donna con l’aureola, lui tatuato in jeans, lei con un vestito bianco e una collana di perline, che sembra una corona di rosario. L’allusione a Gesù e Maria si trae dalle frasi esclamative: "Gesù, che pantaloni!", "Gesù, Maria! Cosa indossate!", "Cara Maria, che vestito!" (segue). Sometimes freedom of expression overrides public morals: the case of advertising ABSTRACT: This article examines the case Sekmadienis v. Lithuania, where the European Court of human rights found that the advertisements by a clothing company, despite using models and captions referring to “Jesus” and “Mary”, did not offend public morals. Nevertheless the balancing in favour, for once, of freedom of expression is due not to a revirement but, essentially, to two factors: the advertisements neither were gratuitously offensive nor incited hatred and, on the other hand, domestic authorities did not provide sufficient justifications for why such use of religious symbols would had been contrary to public morals. Therefore, it’s an assertion not of secularism in front of religion but – the author says quoting Pier Paolo Pasolini - a new laicity, that does not compete with religion: the advertising laicity, born in middle-class entropy.